Computed tomography-guided percutaneous cutting needle biopsy for small (⩽ 20 mm) lung nodules. Issue 46 (November 2017) - Li, Guang-Chao; Fu, Yu-Fei; Cao, Wei; Shi, Yi-Bing; Wang, Tao
Abstract : Abstract: The goal of this study is to determine the feasibility, diagnostic accuracy, and risk factor of complications of computed tomography (CT)-guided percutaneous cutting needle biopsy (PCNB) for small lung nodules. From January 2014 to May 2015, 141 patients with small lung nodule were performed with CT-guided PCNB procedure. Data on technical success, diagnostic accuracy, and complication were collected and analyzed. Technical success of CT-guided PCNB for small lung nodules was 100%. A total of 141 nodules were punctured. The mean time of the procedure was 15.7 ± 4.3 minutes. The PCNB results included malignancy (n = 79), suspected malignancy (n = 6), specific benign lesion (n = 8), nonspecific benign lesion (n = 47), and invalid diagnosis (n = 1). The final diagnosis of the 141 nodules included malignancy (n = 90), benign (n = 37), and nondiagnostic lesion (n = 14). The nondiagnostic nodules were not included for calculating the diagnostic accuracy. The sensitivity, specificity, and overall diagnostic accuracy of CT-guided PCNB for small lung nodule were 94.4% (85/90), 100% (37/37), and 96.1% (122/127), respectively. Pneumothorax and lung hemorrhage (≥ grade 2) occurred in 17 (12.1%) and 22 (15.6%) patients, respectively. Based on the univariate and multivariate logistic analyses, the risk factors of pneumothorax included nonprone position ( P  = .019) and longer procedure time ( P  = .018). The independent risk factor of lung hemorrhage (≥ grade 2) was deeper lesion distance from pleura along needle path ( P  = .024). This study demonstrates that CT-guided PCNB can provide a high diagnostic accuracy for small lung nodule with acceptable complications.